Viral Justice and Public Pressure: An Analysis of the Role of Social Media in Handling Cases of Sexual Violence in Indonesia - Henny Saida Flora (Journal of Politica Governo, 2026)
Sexual violence remains a persistent and under-prosecuted crime in Indonesia, where survivors frequently encounter institutional inertia, evidentiary hurdles, and social stigma that stall formal legal processes. Over the past five years, social media platforms have emerged as an alternative arena in which survivors, activists, and the wider public expose stalled cases, mobilize sympathy, and generate what scholars term "viral justice" or the "no viral, no justice" phenomenon. This article synthesizes recent Indonesian and international scholarship (2021-2026) to analyze how digital virality and public pressure shape the handling of sexual violence cases by police, prosecutors, and courts. Using a systematic narrative literature review of twenty-five peer-reviewed sources selected through a PRISMA-informed screening process, the study identifies four recurring themes: the mechanics of viral escalation, the accelerating effect of public pressure on institutional response, the risks of justice reduction and digital vigilantism, and emerging regulatory and digital-literacy countermeasures. The findings indicate that virality can shorten institutional response time and increase case visibility, but it simultaneously threatens due process, equality before the law, and victim privacy when it substitutes for, rather than supplements, procedural justice. The article concludes by proposing a balanced framework that channels public digital pressure into accountability mechanisms without displacing formal legal safeguards.